Knowledge About Menstruation With Hygiene Behavior During Menstruation In Adolescent Girls At State Senior High School 1 Buko Banggai Islands Regency - Dahlan, Monalysa; Chandra Wahyuni (Universitas STRADA Indonesia, 2016)
Adolescent girls are susceptible to reproductive organ infections. This occurs due to lack of behavior in maintaining personal hygiene, especially during menstruation. Adolescent girls have a low level of attention regarding reproductive health. The design of this study useda descriptive method with a cross-sectional approach. Respondents were taken using a simple random sampling technique. The population studied were 91 female students in grades X and XI at SMA Negeri 1 Buko, Banggai Islands Regency, and the sample was 74 people. The results were analyzed using the chi square statistical test. The results showed that respondents with good knowledge who had positive hygiene behavior during menstruation were 19 (26.6%), respondents with poor knowledge mostly had negative behavior during menstruation as many as 30 (40.5%). The results of data analysis showed that the level of significance was 0.002 <α = 0.05 so that H0 was rejected and H1 was acceptedthusIt can be concluded that there is a significant relationship between knowledge of menstruation and hygiene behavior during menstruation in female adolescents at SMA Negeri 1 Buko. It is expected that the provision of health education about menstruation and hygiene behavior during menstruation can be beneficial for respondents.